Effectiveness of CoronaVac and BNT162b2 Vaccines Against Severe Acute Respiratory Syndrome Coronavirus 2 Omicron BA.2 Infections in Hong Kong . (2nd September 2022) - Yang, Bingyi; Wong, Irene O L; Xiao, Jingyi; Tsang, Tim K; Liao, Qiuyan; Cowling, Benjamin J
Abstract: There is limited evidence on vaccine effectiveness against asymptomatic or mild Omicron infections. We estimated that recent third doses of messenger RNA or inactivated vaccines reduced the risk of self-reported infection by 52% (95% confidence interval, 17%–73%) among randomly sampled adults during the Omicron BA.2–dominated surge in Hong Kong. Abstract : Using self-reported vaccination and testing results for coronavirus disease 2019 among a random adult population in Hong Kong, we estimated that third doses of messenger RNA or inactivated vaccines could provide moderate level of protection during the Omicron BA.2 surge.